Spatio-temporal analysis of the effects of biogas production on agricultural lands. (March 2021) - Kyere, Isaac; Astor, Thomas; Graß, Rüdiger; Fricke, Thomas; Wachendorf, Michael
Highlights: Share of maize area increase is driven by biogas plant capacity. Field edge density decrease is associated with biogas production. Field data and Landsat images, provide a means to study the effects of biogas production on agricultural land. Abstract: With the subsidization of energy crops in Germany by the Renewable Energy Act, the production of biogas became increasingly dependent on agricultural land for biomass generation. The effects of increasing biogas plants' capacities on the increase of maize and other energy crops area over the years have raised sustainability concerns in the German society. A periodic assessment of the impacts of biomass production is necessary to determine efficient and environmentally sustainable recommendations for future planning processes. Previous studies have neglected the effects of biogas plant capacity, which is directly linked with the amount of biomass required and, thus, is supposed to be a driver for the impacts of biogas production on agricultural lands. Combining the Integrated Administration and Control System (IACS) and Landsat satellite data provides a means to study present and past agricultural landscape. The aim of the study was to map the agricultural lands of Northern Hesse from 2000 to 2015, evaluate the change in maize area and structural diversity (i.e. field edge density) of agricultural fields, and assess if biogas production is a major driver of possible changes. Northern Hesse was consciously chosen, as it represents a typical European low-mountain range region with substantial geographical and agricultural variability. Our results show that from 2000 to 2015 on average, the shares of grassland and summer crops areas decreased by 5.7 percentage points (p.p.) and 5.8 p.p., respectively, while the shares of winter crops and maize areas increased by 9.2 p.p. and 2.2 p.p., respectively. Potential drivers of the change in maize area and structural diversity of agricultural fields, such as the mean capacity of biogas plants (kW), and topographical attributes, such as mean elevation (m) and slope (%) were employed as explanatory variables on a municipality level in multiple linear regression models. The mean biogas capacity and elevation were the most significant drivers of change in maize area (p < 0.05), while biogas capacity and slope were the significant drivers of the change in structural diversity. Maize area increased with an increasing capacity of biogas plants at lower elevations of the study area (p < 0.05). A decrease in the structure of fields, which is an indicator for species and habitat diversity, was observed and this was very much associated with the extent of maize and winter crop production. However, the drivers of the changes in the maize area and structure of fields were of low dimensions with model R 2 of 0.21 and 0.35 respectively. Overall, our study demonstrates the potential of spatial data from different origins in mapping land-cover over longer time periods for monitoring bio-economy effects on agricultural landscape.